Identifikasi Kebutuhan Bahan Ajar Digital Berbasis Website pada Mata Pelajaran IPA di SMP Negeri 2 Lembang Kabupaten Pinrang - Risma Risma; Nurhikmah H (Departement of Mathematics Education, 2023)
This study aims to identify the need for website-based digital teaching materials in Natural Sciences subjects at SMP Negeri 2 Lembang in Pinrang Regency. This type of research is quantitative using a descriptive approach, The location of the research was conducted in the village of Pajalele, Kec. Lembang, Chief. Pinrang with research subjects is class VIII B with 22 students and class VIII Natural Sciences teachers. The research instrument used in collecting the required data using the quantifier, about the test. The data collection techniques used in this study are observation, quantifier, test and documentation. The results of this study show that the problem experienced by students is the lack of learning resources in the form of textbooks that do not match the number of students, school facilities in the form of internet access and tablets that are not properly utilized, The data on student learning needs analysis was obtained from average student presentation data that answered Yes and agreed to use website-based digital teaching materials and which were more variable by 78.57%, In addition to analysis of student learning needs, analysis of student learning characteristics was also conducted. Data showed that students were interested in using teaching materials that were more innovative, interesting and usable at any time and place.